Penilaian Kinerja Guru Produktif Dalam Melaksanakan Standar Kompetensi Guru - Dedi Setiawan; Hendra Dani Saputra; Muslim Muslim; R Chandra (invotek, 2020)
Abstract— This study aims to assess teachers in education. This type of research is combination research (quantitative and qualitative). Research subjects were 55 people. The research data was obtained through questionnaires, peers, interviews, and data from the analysis using a percentage formula. The results of the study found that pedagogic competence: (1) For the questionnaire the average total score was 4.2. (2) For peer rankings average total score of 4.0, with the achievement level of respondents 80% remaining in the "good" category, (3) Average productivity score of 4.0, with an achievement level of respondents 80% in the category " good ", and (4) For the results of interviews that discuss the principal, curriculum curriculum and 7 heads of productive majors, with the conclusion of the" good "category. While for the competence of the soul is obtained (1) For the questionnaire the total score is 4.3. (2) For the rank of peers the average total score is 4.2, with the achievement level of respondents 84% ​​in the "good" category, (3) Average productivity score 4.1, with 82% respondents' achievement in the category " good ", and (4) For the results of interviews that discuss the principal, curriculum curriculum and 7 heads of productive departments with the" good "category.